#TITLE_ALTERNATIVE# - AGHNIA, HILMAN
Ocean Thermal Energy Conversion (OTEC) is an ocean thermal energy conversion to electrical energy which is using sea temperature difference cycle between the sea surface and the deep layer, with the difference in temperature (?T) at least 20 degrees C. OTEC is suitable to be built in Indonesia; because Indonesia is located on equatorial, there are a lot of small islands, straits, and varied topography. The mapping of ocean thermal potential in Indonesia is conducted by using the statistics of the monthly rate temperature of the sea surface in the year 1995-2007 with the average of monthly temperature in the sea at the depth of 600 meters, 800 meters, and 1000 meters. The result of data processing shows that the rate of ?T at the depth of 1000 meters in Indonesia in each season varies between 21.5 degrees C-24.5 degrees C in the Western Indonesia and 21.5 degrees C-26.5 degrees C in the Eastern Indonesia. From the map of OTEC potential in Indonesia, it was taken 5 areas based on the highest average rate of ?T; there are North Bali, West Mamuju, Poso, South Ambon, and Halmahera. From those five potential areas, the most potential area to build OTEC is Poso Gulf because the variation of its annual rate average is the smallest, and it is not affected by El-NiÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚ÂƒÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â±o, with the percentage rate of ?T>20 degrees C at the depth of 600 meters, 800 meters and 1000 meters is 100%. The average rate of ?T at the depth of 600 meters is 23.18 degrees C, at the depth of 800 meters is 24.73 degrees C, and at the depth of 1000 meters is 25.46 degrees C.